A method for preparing biomass-based porous carbon suitable for electrolyte ion storage

Through the pretreatment and modulation of biomass raw materials, combined with low-temperature and high-temperature collaborative catalysis technology, porous carbon with a graded porous structure was prepared, which solved the problems of low production efficiency and large carbon emissions of biomass-based porous carbon in the existing technology, and achieved the Industrial production of high-performance electrolyte ion storage materials.

CN118711996BActive Publication Date: 2024-12-13CHANGCHUN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411206473.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2024-12-13
Estimated Expiration
2044-08-30

AI Technical Summary

Technical Problem

It is difficult to effectively prepare high-performance biomass-based porous carbon for storage of large-sized electrolyte ions, and traditional methods have problems with low yields and large carbon emissions, which cannot meet the industrial production requirements of energy storage materials.

Method used

The biomass raw material pretreatment and modulation, combined with low-temperature dehydration pre-carbonization and medium-high temperature synergistic catalytic dehydration carbonization activation technology, porous carbon with a hierarchical porous structure was prepared through double-atmosphere and double-temperature step-regulated heat treatment.

Benefits of technology

Improve the purity and uniformity of porous carbon, enhance compatibility with large-sized electrolyte ions, optimize the production process, reduce costs, and broaden the application fields, solving the traditional method's "high input and low output" question.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118711996B_ABST
    Figure CN118711996B_ABST
Patent Text Reader

Abstract

The present invention is applicable to the technical field of carbon materials, and provides a method for preparing biomass-based porous carbon suitable for electrolyte ion storage, comprising the following steps: crushing, sieving, washing and drying biomass raw materials to obtain biomass powder raw materials; mixing biomass powder with inorganic ammonium salt and ZnCl2, drying and grinding to obtain biomass impregnation products; performing stepwise heat treatment of dual atmosphere and dual temperature regulation on the biomass impregnation products to obtain synergistic catalytic dehydration carbonization activation products; acid washing, washing, drying and crushing the synergistic catalytic dehydration carbonization activation products to obtain biomass-based porous carbon suitable for large-size electrolyte ion storage. The present invention enriches the microscopic nanopore structure of porous carbon through a simple and easy-to-operate synergistic catalytic dehydration one-step carbonization activation process, which is more suitable for the storage and migration of large-size electrolyte ions, and at the same time, significantly improves the yield and greatly reduces carbon emissions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of carbon materials, and in particular relates to a method for preparing biomass-based porous carbon suitable for electrolyte ion storage. Background Art

[0002] Supercapacitors and ion hybrid capacitors have broad application prospects in portable electronic devices, electric vehicles, and equipment requiring ultra-high charging and discharging due to their advantages such as high power density and long cycle life.

[0003] Inorganic salt aqueous solutions as electrolytes can greatly improve the device's withstand voltage and widen the voltage window, thereby increasing the device's energy density. However, there are still great challenges in the efficient storage of larger inorganic salt electrolyte ions.

[0004] Biomass-based porous carbon materials are currently the most widely used carbon electrode materials due to their large specific surface area, good three-dimensional network porous structure, good conductivity and heteroatom doping. However, commercial carbon-based electrode materials are mainly imported and expensive, and most of them are high specific surface area and high microporosity carbon materials, which is not conducive to large-sized electrolyte ions (SO4 2- 、Zn 2+ How to prepare high-performance porous carbon materials suitable for large-size electrolyte ion storage while controlling costs has become a difficult problem facing China's energy storage industry.

[0005] Straw biomass has a natural linear vascular bundle structure. Through reasonable carbonization and activation processes, a good hierarchical porous structure and high mesoporosity can be obtained. However, the current preparation method has the problems of low yield and large carbon emissions, which pollutes the environment and cannot meet the industrial production requirements of energy storage porous carbon. Therefore, a preparation method of biomass-based porous carbon suitable for electrolyte ion storage is proposed. Summary of the invention

[0006] The object of the present invention is to provide a method for preparing biomass-based porous carbon suitable for electrolyte ion storage, aiming to solve the problems raised in the above background technology.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] A method for preparing biomass-based porous carbon suitable for electrolyte ion storage comprises the following steps:

[0009] Step 1, raw material pretreatment: pre-treating the biomass raw material to obtain a clean and dry biomass powder raw material, wherein the pre-treatment process includes crushing, sieving, washing and drying the biomass raw material;

[0010] Step 2, raw material pretreatment modulation: the biomass powder raw material is modulated, the biomass powder is mixed with an inorganic ammonium salt (low-temperature dehydration pre-carbonization agent) and ZnCl2 (medium-high temperature synergistic catalytic dehydration carbonization activator), and the modulated biomass impregnation product is obtained by drying and grinding;

[0011] Step 3, synergistic catalytic dehydration carbonization activation: subjecting the biomass impregnation product to a stepwise heat treatment with dual atmosphere and dual temperature regulation to obtain a synergistic catalytic dehydration carbonization activation product;

[0012] Step 4, post-treatment: acid-washing, water-washing, drying and pulverizing the synergistic catalytic dehydration carbonization activation product to obtain a biomass-based porous carbon suitable for large-size electrolyte ion storage.

[0013] Furthermore, in the screening step, the pulverized biomass raw material is passed through a 40-200 mesh sieve.

[0014] Furthermore, in the raw material pretreatment modulation step, the inorganic ammonium salt includes one or more of NH4Cl, (NH4)2SO4 and NH4NO3; the concentration of the inorganic ammonium salt is 1.0-20.0 wt%; the solid-liquid ratio of the biomass powder raw material and the inorganic ammonium salt aqueous solution is 1:3-30; the mixing method of the biomass powder raw material and the inorganic ammonium salt is solution impregnation.

[0015] The ratio of biomass powder raw material to ZnCl2 is 1:0.5-10; the mixing method of biomass powder raw material and ZnCl2 is impregnation or dry mixing.

[0016] Furthermore, in the raw material pretreatment modulation step, the biomass powder raw material is impregnated and mixed with the inorganic ammonium salt and ZnCl2 for 0.5-24 h, and the impregnated biomass powder raw material is dried at a temperature of 40-90° C. for 1-24 h.

[0017] Further, in the synergistic catalytic dehydration carbonization activation step, the dual atmosphere includes an oxygen-containing atmosphere and an oxygen-free inert atmosphere, wherein the oxygen-containing atmosphere used in the low-temperature dehydration pre-carbonization stage of the inorganic ammonium salt includes one or more of air, oxygen, and an oxygen-nitrogen mixture, and the oxygen-free inert atmosphere used in the high-temperature synergistic catalytic dehydration carbonization activation of ZnCl2 includes one or more of nitrogen, argon, and carbon dioxide; the gas flow rate of the oxygen-containing atmosphere is 10-200 mL / min, and the gas flow rate of the oxygen-free inert atmosphere is 10-200 mL / min;

[0018] The precarbonization temperature of the low-temperature dehydration precarbonization stage of inorganic ammonium salt is 100-500 ℃, the precarbonization time is 0.2-5h, and the heating rate is 0.1-10 ℃ / min; after the low-temperature dehydration precarbonization stage, the oxygen-containing atmosphere is switched to an oxygen-free inert atmosphere, and the precarbonization product is heated from the precarbonization temperature to the activation temperature. The activation temperature of the ZnCl2 medium- and high-temperature synergistic catalytic dehydration carbonization activation stage is 250-1000 ℃, the activation time is 0.5-10 h, and the heating rate is 1-20 ℃ / min.

[0019] Furthermore, in the post-treatment step, after the synergistic catalytic dehydration carbonization activation product is cooled to room temperature, it is successively pickled, washed with water, dried and crushed to obtain porous carbon; the acid solution used in the pickling step includes one or more of hydrochloric acid, sulfuric acid and nitric acid, with a concentration of 0.1-5.0 mol / L; after one pickling and multiple water washings, the filtrate has a pH of 7; in the crushing step, the particle size D 90 10-50 µm.

[0020] Furthermore, the biomass raw material is any one of wheat straw, corn straw, rice straw, rice husk and reed.

[0021] A porous carbon prepared according to the preparation method described above, wherein the yield of the porous carbon is 20-40 wt%.

[0022] Furthermore, the microstructure of the porous carbon is a hierarchical porous structure; the hierarchical porous structure includes micropores, mesopores and macropores, wherein the micropores are divided into two levels: small-sized micropores (0.4-1.3 nm) and large-sized micropores (1.3-2 nm); the mesopores are distributed in 2-50 nm; and the macropores are distributed above 50 nm. This hierarchical porous distribution plays a vital role in the adsorption and storage of large-sized electrolyte ions.

[0023] An application of the porous carbon described above in the preparation of a capacitor, wherein the porous carbon has a specific capacitance of ≥230 F / g in a salt solution system supercapacitor, a capacity retention rate of ≥80% when the current density increases from 0.5 A / g to 20 A / g, an energy density of ≥18 Wh / kg, and a capacity loss of ≤0.1% after 10,000 charge and discharge cycles at a current density of 1 A / g;

[0024] The specific capacity of the porous carbon in the salt solution system ion hybrid capacitor is ≥130 mAh / g, and the energy density is ≥95 Wh / kg;

[0025] The salt solution system includes one or more of NaCl, KCl, Na2SO4, ZnSO4, KNO3, and NaNO3; the concentration of the electrolyte is 0.5-8 mol / L.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] The present invention proposes a method for preparing porous carbon by synergistic catalytic carbonization and activation, which is simple and easy to implement. Before carbonization and activation, the purity and uniformity of the biomass porous carbon are significantly improved by pre-treating and modulating the raw materials. In addition, the method effectively prepares porous carbon with a hierarchical porous structure through dual-atmosphere, dual-temperature step-by-step heat treatment, enhancing its good compatibility with large-sized electrolyte ions. This method not only optimizes the production process, but also broadens the application field of biomass-based porous carbon, solving the previous industrial problem of "high input and low output". BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 Flow chart of preparing porous carbon in Example 1.

[0029] Figure 2 This is a scanning electron microscope image of the porous carbon prepared in Example 1.

[0030] Figure 3 The isothermal adsorption-desorption curve and pore size distribution diagram of the porous carbon prepared in Example 1; (a) is the isothermal adsorption-desorption curve diagram, and (b) is the pore size distribution diagram.

[0031] Figure 4 This is a constant current charge and discharge curve of the porous carbon prepared in Example 1 as an electrode material in a zinc ion hybrid capacitor in a ZnSO4 electrolyte system; the six charge and discharge lines from left to right in the figure represent 10, 5, 2, 1, 0.5, and 0.2 A / g respectively.

[0032] Figure 5 This is a graph of the specific capacity of the porous carbon prepared in Example 1 as an electrode material at different current densities in a zinc ion hybrid capacitor in a ZnSO4 electrolyte system.

[0033] Figure 6 This is a rate performance diagram of the porous carbon prepared in Example 1 as an electrode material in a supercapacitor in a Na2SO4 electrolyte system.

[0034] Figure 7 The energy density and power density diagram of the porous carbon prepared in Example 1 as the electrode material in the supercapacitor of the Na2SO4 electrolyte system.

[0035] Figure 8 This is a cycle life diagram of the porous carbon prepared in Example 1 as an electrode material in a supercapacitor in a Na2SO4 electrolyte system.

[0036] Fig. 9This is a cycle life diagram of a zinc ion hybrid capacitor using the porous carbon prepared in Example 1 as the positive electrode material in a ZnSO4 electrolyte system.

[0037] Fig.10 This is a diagram showing the energy density and power density of the porous carbon prepared in Example 1 as the positive electrode material in a zinc ion hybrid capacitor in a ZnSO4 electrolyte system. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0039] One embodiment of the present invention provides a method for preparing biomass-based porous carbon suitable for electrolyte ion storage, comprising the following steps:

[0040] 1) Raw material pretreatment: The biomass raw materials are crushed, screened, washed and dried to obtain clean and dry biomass powder raw materials. Raw material pretreatment solves the problems of complex biomass composition, irregular particles, low equipment utilization, unstable electrochemical performance, etc.

[0041] The biomass raw material in the crushing step is passed through a 40-200 mesh sieve. The particle size of the raw material will affect the efficiency of the synergistic catalytic dehydration process, the uniformity and stability of the porous carbon hierarchical porous structure, and the adjustment of experimental parameters and the setting of optimal parameters during the carbonization activation process.

[0042] 2) Raw material pretreatment and modulation: The biomass powder raw material is impregnated, specifically including the mixing and drying of the low-temperature dehydration pre-carbonization agent and the medium-high temperature synergistic catalytic dehydration carbonization activator. The low-temperature dehydration pre-carbonization agent and the medium-high temperature synergistic catalytic dehydration carbonization activator can fully penetrate into the pores and organizational structure of the biomass to produce a porous carbon material with a high specific surface area, excellent hierarchical porous structure, high yield, low carbon emissions, and high electrochemical performance.

[0043] Among them, the low-temperature dehydration pre-carbonizing agent is an inorganic ammonium salt, and the inorganic ammonium salt includes one or more of NH4Cl, (NH4)2SO4, and NH4NO3. The mixing method of the biomass powder raw material and the inorganic ammonium salt is solution impregnation, the concentration of the inorganic ammonium salt is 1.0-20.0 wt%, the solid-liquid ratio of the inorganic ammonium salt aqueous solution to the biomass powder is 1:3-30, and the impregnation time is 0.5-24 h.

[0044] Among them, the medium-high temperature synergistic catalytic dehydration carbonization activator is ZnCl2, the mixing method of the biomass powder raw material and ZnCl2 is impregnation or dry mixing, and the ratio of the biomass powder raw material to ZnCl2 is 1:0.5-10.

[0045] The biomass powder raw material is impregnated with inorganic ammonium salt and ZnCl2 for 0.5-24 h, and the impregnated biomass powder raw material is dried at a temperature of 40-90°C for 1-24 h to obtain a biomass impregnation product.

[0046] The low-temperature dehydration pre-carbonization agent and the medium-high temperature synergistic catalytic dehydration carbonization activator used in the present invention are both commonly used inorganic salts, which are low in cost and non-corrosive to equipment. In addition, the two reagents will not chemically react with each other, so they can be added simultaneously in a certain proportion to complete the impregnation in one step. This reduces the steps, improves the efficiency, and has strong applicability.

[0047] 3) Synergistic catalytic dehydration carbonization activation: In a tubular furnace, the impregnation product is subjected to dual-atmosphere, dual-temperature step-regulated heat treatment to obtain a synergistic catalytic dehydration carbonization activation product.

[0048] Among them, the low-temperature dehydration pre-carbonization stage is carried out in an oxygen-containing atmosphere (including one or more of air, oxygen, and oxygen-nitrogen mixture). The biomass impregnation product is first loaded into an open corundum crucible, then placed in a tubular furnace, introduced into an oxygen-containing atmosphere, and slowly heated to the low-temperature catalytic dehydration temperature for pre-carbonization treatment. Among them, the pre-carbonization temperature is 100-500 ℃, the pre-carbonization time is 0.2-5 h, and the heating rate is 0.1-10 ℃ / min. After the low-temperature dehydration pre-carbonization stage is completed, the oxygen-containing atmosphere is switched to an oxygen-free inert atmosphere (including one or more of nitrogen, argon, and carbon dioxide), and a medium-high temperature synergistic catalytic dehydration carbonization activation treatment is carried out under the protection of an inert atmosphere. The protective atmosphere is nitrogen or argon, the activation temperature is 250-1000 ℃, the activation time is 0.5-10 h, and the heating rate is 1-20 ℃ / min.

[0049] 4) Post-treatment: After the sample is cooled to room temperature, a certain amount of acid solution is used to remove excess activator and metal impurities, and then it is washed with deionized water for multiple times until the filtrate pH is 7, and finally dried and crushed to obtain porous carbon with a hierarchical porous structure. The acid used in the pickling step includes one or more of hydrochloric acid, sulfuric acid, and nitric acid, with a concentration of 0.1-5 mol / L; the particle size D in the crushing step 90 10-50 µm.

[0050] In the embodiment of the present invention, the main components of biomass are: cellulose, hemicellulose and lignin. Straw-based biomass contains more cellulose and lignin, and therefore contains more H and O elements, and has a loose texture. Direct pyrolysis and carbonization will lead to the emission of a large amount of CO, CO2, CH4 and other carbon-containing small molecule gases. Therefore, the present invention performs a step-by-step heat treatment with dual atmospheres and dual temperature adjustments. Through the low-temperature dehydration pre-carbonization stage, inorganic ammonium salts allow more H and O elements in the biomass molecules to be directly removed from the carbon skeleton in the form of water molecules, thereby avoiding the loss of a large amount of C elements in the form of carbon-containing small molecule gases or tars along with H and O elements during the pyrolysis and carbonization process, effectively fixing C in the carbon skeleton, improving the density and yield of carbon, and regulating the biochar from a molecular level. sp 2 The carbon matrix structure is improved, thereby improving some of its physical and chemical properties, maximizing the value of the pyrolysis carbonization products of biomass straw. ZnCl2 synergistically catalyzes dehydration in the medium temperature zone, coupled with the catalytic dehydration of inorganic ammonium salts, to form a stable sp 2 The carbon matrix structure then plays the role of activation and pore formation in the high temperature zone, and finally forms an excellent hierarchical porous structure. Through the synergistic catalytic dehydration effect, the carbon yield is increased by 10-25% compared with the traditional carbonization activation process, which reduces the cost to a certain extent and also greatly reduces the production of greenhouse gases. At the same time, the doping of heteroatoms such as N and O in the carbon skeleton will increase the wettability of the material to a certain extent, and the increase in pseudocapacitance will further improve the specific capacity of the electrode material. Therefore, the synergistic catalytic dehydration carbonization activation technology of the present invention is of great significance to the large-scale production of biomass-based porous carbon materials.

[0051] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.

[0052] Example 1: A method for preparing biomass-based porous carbon suitable for electrolyte ion storage, such as Figure 1 As shown, the steps are as follows:

[0053] (1) Raw material pretreatment: The biomass raw material corn stalk was crushed with a crusher and passed through an 80-mesh sieve. Then it was immersed in an appropriate amount of deionized water for washing. After washing three times, it was filtered and dried at 90 °C for 12 h to obtain pretreated corn stalk powder.

[0054] (2) Raw material pretreatment: Weigh 2 g of the above-pretreated corn straw powder, 2 g of NH4Cl and 4 g of ZnCl2 respectively into a beaker, add 20 mL of deionized water, stir thoroughly, seal and soak at room temperature for 12 h, then dry the soaked corn straw at 80 ℃ for 24 h and grind for 30 min for later use.

[0055] (3) Synergistic catalytic dehydration carbonization activation: The above pre-treated sample was placed in a corundum crucible, opened and placed in a tube furnace, and air was passed through at a flow rate of 20 mL / min for low-temperature dehydration pre-carbonization treatment: the temperature was raised from room temperature to 250 °C at a rate of 1 °C / min, and the temperature was kept at this temperature for 30 min. Then, the air was quickly switched to nitrogen protective gas (air flow rate of 20 mL / min), and the temperature was raised to 850 °C at a rate of 5 °C / min, and the temperature was kept at the activation temperature for 2 h.

[0056] (4) Post-treatment: After activation is completed and cooled to room temperature, the sample is taken out and the sample cooled to room temperature is added with 1 mol / L HCl solution at a solid-liquid ratio of 1:50 to remove excess activator and metal impurities. The sample is then washed with deionized water several times until the filtrate pH is 7, dried at 100 °C for 12 h, and finally crushed to obtain graded porous carbon.

[0057] Figure 2 This is a scanning electron microscope image of the porous carbon prepared in Example 1. It can be seen that its morphology is full of three-dimensional macroporous structures. This staggered pore structure can serve as a storage pool for large-sized electrolyte ions, which is beneficial to the performance of its capacitance.

[0058] Figure 3 The isothermal adsorption-desorption curve (a) and pore size distribution diagram (b) of the porous carbon prepared in Example 1. Figure 3 It can be seen from (a) that the adsorption-desorption isotherm shows a Typc-Ⅱ type based on the IUPAC classification, and the hysteresis loop belongs to the H4 type hysteresis loop, which is mainly contributed by mesopores. It can be seen that the porous carbon prepared under this condition is a porous material dominated by mesopores. Figure 3 As can be seen in (b), the micropores of the hierarchical porous carbon are concentrated at around 0.9 nm and 1.6 nm, the mesopores are concentrated at around 3.8 nm, and a nano-graded pore structure of 0.8-1.2 nm, 1.3-1.8 nm and 2-5 nm is formed. Together with the macropores of 50-100 nm, a 4-level pore structure distribution is formed. This hierarchical pore structure is more conducive to ion transport during the charge and discharge process.

[0059] The graded porous carbon material prepared in Example 1 was prepared into an electrode sheet as the positive electrode and a zinc sheet as the negative electrode, and placed in a 2 M ZnSO4 electrolyte. The battery charge and discharge tester was used to perform charge and discharge tests at different current densities. Figure 4 It can be seen that the charge-discharge curve shows a symmetrical isosceles triangle shape, indicating excellent reversibility during the charge-discharge process. Figure 5It can be seen that the specific capacity of the zinc ion hybrid capacitor can reach 135.6 mAh / g at 0.2 A / g. After cycling at different current densities of 0.2-10 A / g, the specific capacity can reach 132.1 mAh / g when charged and discharged again at a current density of 0.2 A / g, and the specific capacity retention rate is as high as 97.4%. Fig. 9 It can be seen that after 2500 charge and discharge cycles at a current density of 1 A / g, its capacitance retention rate is as high as 100%, and its coulombic efficiency is also as high as 100%. Fig.10 It can be seen that at a current density of 0.2A / g, its energy density is 99.6 Wh / kg and its power density is 412.1 W / kg.

[0060] The graded porous carbon material prepared in Example 1 was prepared into an electrode sheet as the positive electrode and a zinc sheet as the negative electrode, and placed in a 2 M Na2SO4 electrolyte. Figure 6 It can be seen that the specific capacitance of porous carbon in the Na2SO4 electrolyte system supercapacitor is 235.32 F / g, and when the current density increases from 0.5 A / g to 20 A / g, the capacitance retention rate is as high as 80.5%. Figure 7 It can be seen that at a current density of 0.5 A / g, its energy density is 18.43 Wh / kg and its power density is 208.1 W / kg. Figure 8 It can be seen that after 10,000 charge and discharge cycles at a current density of 1 A / g, its capacitance retention rate is still as high as 99.8% and its Coulomb efficiency is as high as 99.9%.

[0061] Table 1 is a summary table of the properties of the porous carbon prepared in Example 1 of the present invention:

[0062]

[0063] Example 2: In this example, corn stalks, a biomass raw material, are used to prepare graded porous carbon. The difference between this example and the preparation steps of Example 1 is that:

[0064] In the raw material pretreatment preparation step of this embodiment, 2 g of the above-mentioned pretreated corn stalk powder, 1 g of NH4Cl and 4 g of ZnCl2 were weighed into a beaker, 20 mL of deionized water was added, and after sufficient stirring, the mixture was sealed and immersed at room temperature for 12 h.

[0065] The remaining steps are exactly the same.

[0066] Example 3: In this example, corn stalks, a biomass raw material, are used to prepare graded porous carbon. The difference between this example and the preparation steps of Example 1 is that:

[0067] In the raw material pretreatment preparation step of this embodiment, 2 g of the above-mentioned pretreated corn straw powder, 3 g of NH4Cl and 4 g of ZnCl2 were weighed into a beaker, 20 mL of deionized water was added, and after sufficient stirring, the mixture was sealed and immersed at room temperature for 12 h.

[0068] The remaining steps are exactly the same.

[0069] Example 4: In this example, corn stalks, a biomass raw material, are used to prepare graded porous carbon. The difference between this example and the preparation steps of Example 1 is that:

[0070] In the raw material pretreatment preparation step of this embodiment, 2 g of the above-mentioned pretreated corn stalk powder, 2 g of NH4Cl and 2 g of ZnCl2 were weighed into a beaker, 20 mL of deionized water was added, and after sufficient stirring, the mixture was sealed and immersed at room temperature for 12 h.

[0071] The remaining steps are exactly the same.

[0072] Example 5: In this example, porous carbon is prepared using biomass raw material corn stalks; the difference between this example and Example 1 in the preparation steps is:

[0073] In the activation step of this embodiment, 2 g of the pre-treated corn stalk powder, 2 g of NH4Cl and 6 g of ZnCl2 were weighed into a beaker, 20 mL of deionized water was added, and after sufficient stirring, the mixture was sealed and immersed at room temperature for 12 h.

[0074] The remaining steps are exactly the same.

[0075] Example 6: In this example, porous carbon is prepared using biomass raw material corn stalks; the difference between this example and the preparation steps of Example 1 is:

[0076] In the synergistic catalytic dehydration carbonization activation step of this embodiment, the temperature is raised from room temperature to 150° C. at a heating rate of 0.1° C. / min in an air atmosphere, and the holding time is 5 h.

[0077] The remaining steps are exactly the same.

[0078] Example 7: In this example, porous carbon is prepared using biomass raw material corn stalks; the difference between this example and the preparation steps of Example 1 is:

[0079] In the synergistic catalytic dehydration carbonization activation step of this embodiment, the temperature is raised from room temperature to 350° C. at a heating rate of 2° C. / min in an air atmosphere, and the holding time is 15 min.

[0080] The remaining steps are exactly the same.

[0081] Example 8: In this example, porous carbon is prepared using biomass raw material corn stalks; the difference between this example and the preparation steps of Example 1 is:

[0082] In the synergistic catalytic dehydration carbonization activation step of this embodiment, after the air is switched to nitrogen, the temperature is raised to 750°C at a heating rate of 1°C / min and the activation temperature is maintained for 5 h.

[0083] The remaining steps are exactly the same.

[0084] Example 9: In this example, porous carbon is prepared using biomass raw material corn stalks; the difference between this example and Example 1 in the preparation steps is:

[0085] In the coordinated catalytic dehydration carbonization activation step of this embodiment, after the air is switched to nitrogen protective gas, the temperature is raised to 950° C. at a heating rate of 10° C. / min and kept at the activation temperature for 1 h.

[0086] The remaining steps are exactly the same.

[0087] Example 10: In this example, porous carbon is prepared using biomass raw material corn stalks; the difference between this example and Example 1 in the preparation steps is:

[0088] The biomass raw material used in this embodiment is rice straw. Except for the difference in raw materials, the specific preparation steps are exactly the same as those in Example 1.

[0089] Comparative Example 1: Preparation of a biomass-based porous carbon, the specific preparation steps are as follows:

[0090] (1) Carbonization and activation: The biomass raw material corn stalks were crushed, cleaned and dried. Zinc chloride and corn stalks were dry mixed in a ratio of 1:2, and then heated to 50°C in a nitrogen atmosphere. o The heating rate was increased to 850 C / min. o C, carbonization activation for 1 h.

[0091] (2) Post-treatment: After activation, cool it to room temperature and take it out. Add 1 mol / L HCl at a solid-liquid ratio of 1:50 to remove metal impurities. Then wash it with a large amount of deionized water until the filtrate pH = 7. Dry and crush it to obtain porous carbon.

[0092] Table 2 is a summary table of the yield, specific surface area and specific capacitance of the porous carbon prepared in Examples 1-10 of the present invention and Comparative Example 1:

[0093]

[0094] It can be found from Table 2 that with the increase of specific surface area, the specific capacitance value of ZnSO4 system zinc ion hybrid capacitor continues to increase. When the specific surface area reaches 1990.2 m2 / g, the specific capacitance reaches its maximum value, which is 144.8 mAh / g. After that, the specific capacitance decreases to a certain extent with the increase of specific surface area.

[0095] The above are only preferred embodiments of the present invention. It should be pointed out that, for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention. These should also be regarded as the protection scope of the present invention. These will not affect the effect of the implementation of the present invention and the practicality of the patent.

Claims

1. A method for preparing biomass-based porous carbon suitable for electrolyte ion storage, characterized in that: The following steps are involved: Step 1: Raw material pretreatment: crushing, sieving, washing and drying the biomass raw materials to obtain clean and dry biomass powder raw materials; Step 2, raw material pretreatment and modulation: the biomass powder raw material is mixed with inorganic ammonium salt and ZnCl2, and the modulated biomass impregnation product is obtained by drying and grinding; Step 3, synergistic catalytic dehydration carbonization activation: subjecting the biomass impregnation product to a stepwise heat treatment with dual atmosphere and dual temperature regulation to obtain a synergistic catalytic dehydration carbonization activation product; Step 4, post-treatment: acid-washing, water-washing, drying and pulverizing the synergistic catalytic dehydration carbonization activation product to obtain a biomass-based porous carbon suitable for large-size electrolyte ion storage; The microstructure of the porous carbon is a hierarchical porous structure; the hierarchical porous structure includes micropores, mesopores and macropores, wherein the micropores are divided into two levels: small-sized micropores and large-sized micropores, the small-sized micropores are distributed in 0.4-1.3 nm, the large-sized micropores are distributed in 1.3-2 nm; the mesopores are distributed in 2-50 nm; the macropores are distributed above 50 nm; In the screening step, the crushed biomass raw material is passed through a 40-200 mesh sieve; In the raw material pretreatment modulation step, the inorganic ammonium salt includes one or more of NH4Cl, (NH4)2SO4 and NH4NO3; the concentration of the inorganic ammonium salt is 1.0-20.0 wt%; the solid-liquid ratio of the biomass powder raw material and the inorganic ammonium salt aqueous solution is 1:3-30; the mixing method of the biomass powder raw material and the inorganic ammonium salt is solution impregnation; The ratio of biomass powder raw material to ZnCl2 is 1:0.5-10; the mixing method of biomass powder raw material and ZnCl2 is impregnation or dry mixing; In the raw material pretreatment and modulation step, the biomass powder raw material is impregnated and mixed with the inorganic ammonium salt and ZnCl2 for 0.5-24 hours, and the impregnated biomass powder raw material is dried at a temperature of 40-90°C for 1-24 hours; In the synergistic catalytic dehydration carbonization activation step, the dual atmosphere includes an oxygen-containing atmosphere and an oxygen-free inert atmosphere, wherein the oxygen-containing atmosphere used in the low-temperature dehydration pre-carbonization stage of the inorganic ammonium salt includes one or more of air, oxygen, and a mixture of oxygen and nitrogen, and the oxygen-free inert atmosphere used in the high-temperature synergistic catalytic dehydration carbonization activation of ZnCl2 includes one or more of nitrogen, argon, and carbon dioxide; the gas flow rate of the oxygen-containing atmosphere is 10-200 mL / min, and the gas flow rate of the oxygen-free inert atmosphere is 10-200 mL / min; The pre-carbonization temperature of the inorganic ammonium salt low-temperature dehydration pre-carbonization stage is 100-500 °C, the pre-carbonization time is 0.2-5 h, and the heating rate is 0.1-10 °C / min; after the low-temperature dehydration pre-carbonization stage, the oxygen-containing atmosphere is switched to an oxygen-free inert atmosphere, and the pre-carbonized product is heated from the pre-carbonization temperature to the activation temperature. The activation temperature of the ZnCl2 medium- and high-temperature synergistic catalytic dehydration carbonization activation stage is 250-1000 °C, the activation time is 0.5-10 h, and the heating rate is 1-20 °C / min; In the post-treatment step, after the synergistic catalytic dehydration carbonization activation product is cooled to room temperature, it is successively acid-washed, water-washed, dried and crushed to obtain porous carbon; the acid solution used in the acid-washing step includes one or more of hydrochloric acid, sulfuric acid and nitric acid, with a concentration of 0.1-5.0 mol / L; the particle size D in the crushing step is 90 10-50 µm; The biomass raw material is any one of wheat straw, corn straw, rice straw, rice husk and reed.

2. A porous carbon obtained by the preparation method according to claim 1, characterized in that: The microstructure of the porous carbon is a hierarchical porous structure; the hierarchical porous structure includes micropores, mesopores and macropores, wherein the micropores are divided into two levels: small-sized micropores and large-sized micropores, the small-sized micropores are distributed in 0.4-1.3 nm, the large-sized micropores are distributed in 1.3-2 nm; the mesopores are distributed in 2-50 nm; the macropores are distributed above 50 nm; The yield of the porous carbon is 20-40 wt%.

3. A use of the porous carbon according to claim 2 in preparing a capacitor, characterized in that: The porous carbon has a specific capacitance of ≥230 F / g in a salt solution system supercapacitor, a capacity retention rate of ≥80% when the current density increases from 0.5 A / g to 20 A / g, an energy density of ≥18 Wh / kg, and a capacity loss of ≤0.1% after 10,000 charge and discharge cycles at a current density of 1 A / g; The specific capacity of the porous carbon in the salt solution system ion hybrid capacitor is ≥130 mAh / g, and the energy density is ≥95Wh / kg; The salt solution system includes one or more of NaCl, KCl, Na2SO4, ZnSO4, KNO3, and NaNO3; the concentration of the electrolyte is 0.5-8 mol / L.